Botulinum Toxin Injections for Leg Contouring in East Asians. (October 2020) - Cheng, Judy; Chung, Hye Jin; Friedland, Matthew; Hsu, Sarah Hahn
Abstract : BACKGROUND: A common aesthetic concern among East Asian women is enlarged calves. Although surgical resection has been a traditional treatment option, botulinum toxin injections into the gastrocnemius muscle are an emerging, noninvasive alternative. OBJECTIVE: To perform a literature review on botulinum toxin injections for leg contouring. MATERIALS AND METHODS: A literature review was conducted using PubMed, Web of Science, Embase, and Cochrane's CENTRAL database to identify articles relating to combinations of the terms botulinum toxin, gastrocnemius, calves, and leg contouring. RESULTS: Based on the limited publications to date, the authors prepared a review on how to treat an enlarged calf with botulinum toxin including injection techniques, anticipated efficacy, outcome monitoring, and potential side effects. CONCLUSION: Botulinum toxin injections for calf reduction are an emerging, noninvasive treatment option. Studies to date suggest that it is an efficacious method with few immediate side effects. Future areas for investigation include defining the criteria for calf hypertrophy, minimum effective dosage of botulinum toxin, and the potential long-term effects of injections.